Odpowiedzi

2010-03-01T18:00:40+01:00
A). {3a+a² - [(a-3a² + 2b) - (2a -a² +2b)]} =
={3a+a²-[a-3a²+2b-2a+a²-2b]} =
={3a+a²-a+3a²-2b+2a-a²+2b}=
=3a+a²-a+3a²-2b+2a-a²+2b =
=4a+3a²

b). -[3mk - (k²-2mk + m² )] - (m² - 5mk - 2k² ) =
= -[3mk-k²+2mk-m²] -m²+5mk+2k² =
= -3mk+k²-2mk+m²-m²+5mk+2k²=
= 3k²
1 5 1
2010-03-01T18:04:24+01:00
A). {3a+a² - [(a-3a² + 2b) - (2a -a² +2b)]} ={3a+a²-[a-3a²+2b-2a+a²+2b]}=
={3a+a²-a+3a²-2b+2a-a²-2b}=4a+3a²

b). -[3mk - (k²-2mk + m2 )] - (m² - 5mk - 2k² )=-[3mk-k²+2mk-m²]-m²+5mk+2k²=
=-3mk+k²-2mk+m²+5mk+2k²=3k²

2010-03-01T18:06:29+01:00
{3a+a² - [(a-3a² + 2b) - (2a -a² +2b)]} = {3a+a² - [a - 3a² + 2b -2a + a² -2b]} =
{3a+a² + a + 2a² } = 3a² + 4a

-[3mk - (k²-2mk + m2 )] - (m² - 5mk - 2k² ) = -[3mk - k² + 2mk - 2m - m² + 5mk + 2k²] = -k² + m² - 10km + 2m